2012
DOI: 10.1002/stem.1155
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Choice of Allelic Expression in Human Neural Stem Cells

Abstract: Monoallelic gene expression, such as genomic imprinting, is well described. Less well‐characterized are genes undergoing stochastic monoallelic expression (MA), where specific clones of cells express just one allele at a given locus. We performed genome‐wide allelic expression assessment of human clonal neural stem cells derived from cerebral cortex, striatum, and spinal cord, each with differing genotypes. We assayed three separate clonal lines from each donor, distinguishing stochastic MA from genotypic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 44 publications
6
78
2
Order By: Relevance
“…Autosomal genes can also undergo random monoallelic expression, with initial descriptions of its occurrence in immune genes (Mostoslavsky et al 2001) and the olfactory receptors (Chess et al 1994), providing cellular diversity within these systems. Recent high-throughput allelic expression profiling of human clonal lymphoblastoid, fibroblast, and neural stem cells has shown that stochastic allelic expression is more prevalent than previously thought, affecting up to 10% of autosomal expressed transcripts across a diverse range of cell types (Gimelbrant et al 2007;Chess 2012;Jeffries et al 2012;Li et al 2012;Zwemer et al 2012). This process has also been observed in mouse, with a significant overlap in loci characterized by random monoallelic expression across species (Zwemer et al 2012).…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Autosomal genes can also undergo random monoallelic expression, with initial descriptions of its occurrence in immune genes (Mostoslavsky et al 2001) and the olfactory receptors (Chess et al 1994), providing cellular diversity within these systems. Recent high-throughput allelic expression profiling of human clonal lymphoblastoid, fibroblast, and neural stem cells has shown that stochastic allelic expression is more prevalent than previously thought, affecting up to 10% of autosomal expressed transcripts across a diverse range of cell types (Gimelbrant et al 2007;Chess 2012;Jeffries et al 2012;Li et al 2012;Zwemer et al 2012). This process has also been observed in mouse, with a significant overlap in loci characterized by random monoallelic expression across species (Zwemer et al 2012).…”
Section: Introductionmentioning
confidence: 90%
“…Approximately 7000 autosomal genes contained informative (heterozygous) transcribed SNPs (see Materials and Methods) allowing us to make quantitative allelic expression measurements. Based on previous allelic expression studies (Pastinen et al 2004;Serre et al 2008;Lee et al 2009;Jeffries et al 2012) and Xchromosome inactivation profiles (Supplemental Fig. S2), we categorized the expression of genes as biallelic (BA), allelically skewed, and monoallelic (MA) according to the degree of allelic bias detected.…”
Section: Epigenetic Reprogramming To Induced Pluripotency Resets Randmentioning
confidence: 99%
See 3 more Smart Citations